Health is the first wealth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The article on organic agriculture in Spore 85 drew a lot of comments, including one from Dr Gezahegu Shirmako in Hagere-Selam, Ethiopia. He is dismayed that 'nowadays, teratological disorders [deformations] among domestic animals are mushrooming...